Difficulties in Realizing Regional Finance in Indonesia: Quantitative Descriptive Approach - Kekry, Boy Piter Nizu; Iriawan, Iriawan (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
The focus of this study is a comparison of the realization of regional income and expenditure components for the 2023 fiscal year in Indonesia, while the research focus is on 38 provincial governments, classified according to region. In the western part of Indonesia, there are 23 Provincial Governments, and in the eastern part of Indonesia, there are 15 Provincial Governments. The main research approach is quantitative descriptive, with a data analysis method applying comparative analysis, using the independent sample t-test technique to find a comparison of the averages of two unrelated groups, using the welsh t-test and cohen's t-test coefficient testing techniques. The study findings found the realization of regional finance in Indonesia. First, the fact that the realization of the PAD, TKDD, and PL components in the eastern region tends to be lower compared to the western region of Indonesia. This recognition is justified by comparative statistics through the significance value (< 0.05) of the welsh t-test coefficient and Cohen's coefficient effect. Secondly, the fact that the realization of the BP, BBJ, and BM components in the eastern region is very low compared to the western region of Indonesia, the uniform realization achievement of the two regions in the BL component reaches a realization figure of >80%, this recognition is justified by statistical comparison through the significance value (<0.05) of the welsh's coefficient and cohen's coefficient effect.